1998
DOI: 10.2466/pms.1998.87.3f.1331
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Trait Approach to the Development of Persistent Stuttering

Abstract: The premise that stuttering disorders develop according to the orthogenetic principle, preceding in a continuous, unilinear fashion from a state of relative lack of differentiation to a state of increasing differentiation and hierarchic integration, was examined. Responses to Woolf's Perceptions of Stuttering Inventory of 87 individuals who stutter were analyzed using a Rasch 1980 latent trait model for dichotomously scored data. Analyses of responses indicated struggle, avoidance, and expectation through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Rothenberg's inventory showed high test-retest reliability among adult stuttering speakers, resulting in correlations of .88 for Struggle, .89 for Avoidance, and .85 for Expectancy (as cited in Woolf ). The PSI continues to be a popular measure of clientperceived aspects of stuttering (e.g., Brin, Steward, Blitzer, & Diamond, 1994;Ginsberg, 2000;Gordon et al, 1995;Kalinowski, Kalinowski, Stuart, & Rastatter, 1998;Langevin & Kully, 2003;Lawson, Pring, & Fawcus, 1993;Manning, Dailey, & Wallace, 1984;Webster, 1979). Ginsberg found that participants' self-ratings of stuttering severity were closely associated with their scores on the PSI (correlations ranged from .89 for expectancy to .92 for total perceptions of stuttering).…”
Section: Description Of Inventories and Questionnairesmentioning
confidence: 99%
“…Rothenberg's inventory showed high test-retest reliability among adult stuttering speakers, resulting in correlations of .88 for Struggle, .89 for Avoidance, and .85 for Expectancy (as cited in Woolf ). The PSI continues to be a popular measure of clientperceived aspects of stuttering (e.g., Brin, Steward, Blitzer, & Diamond, 1994;Ginsberg, 2000;Gordon et al, 1995;Kalinowski, Kalinowski, Stuart, & Rastatter, 1998;Langevin & Kully, 2003;Lawson, Pring, & Fawcus, 1993;Manning, Dailey, & Wallace, 1984;Webster, 1979). Ginsberg found that participants' self-ratings of stuttering severity were closely associated with their scores on the PSI (correlations ranged from .89 for expectancy to .92 for total perceptions of stuttering).…”
Section: Description Of Inventories and Questionnairesmentioning
confidence: 99%
“…to complex, highly developed strategies that are pervasive and highly integrated in their daily communication (for example, breathing noisily or with great effort while trying to speak, avoiding talking to parents, pretending to be angry when speaking, etc. ; Kalinowski et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This percept is pervasive, widely held, and resistant to change. Simply put, it is a stereotype that can be found in numerous sub‐populations including 9–11‐year‐old children (Franck et al 2003), middle‐school students (Evans et al 2008), employers (Hurst and Cooper 1983), speech–language pathologists (Cooper and Cooper 1985, Lass et al 1989, Kalinowski et al 1993), those with no previous direct contact with PWS (Craig et al 2003), those who have familial relationships with PWS (for example, parents, relatives, and family members; Crowe and Cooper 1977, Doody et al 1993), and even PWS themselves (Lass et al 1995). Modifications or alterations of the stuttering stereotype appear to be difficult, if not impossible (Leahy 1994, McGee et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, people who stutter avoid using feared sounds or words, speaking over the telephone, speaking with strangers, ordering in a restaurant, etc. (Woolf 1967, Kalinowski et al 1998. They also continue to scan ahead when speaking to replace upcoming difficult words with synonyms that are less likely to be stuttered.…”
Section: Covert Forms Of Stuttering -Levelmentioning
confidence: 99%